2018
DOI: 10.1002/14651858.cd012355.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily long-acting beta₂-agonists/inhaled corticosteroids combined inhalers versus inhaled long-acting muscarinic antagonists for people with chronic obstructive pulmonary disease

Abstract: Based on analysis of primary and secondary outcomes, we are uncertain whether once-daily ICS/LABA, combined in one inhaler, has a different efficacy or adverse effect profile compared to LAMA for treatment of people with COPD. However, the current review is based on only two trials with the main focus on primary outcomes other than those considered in this review. The short follow-up period and the very low quality of evidence limit our confidence in the result and increase uncertainty. Further trials of longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Long-term ICS use has been associated with pneumonia, oral candidiasis, and bone fractures (47). The risk-to-benefit issue warrants further investigation considering that some studies show greater effects of dual bronchodilators on reducing exacerbations than LABA+ICS therapy (63,78).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term ICS use has been associated with pneumonia, oral candidiasis, and bone fractures (47). The risk-to-benefit issue warrants further investigation considering that some studies show greater effects of dual bronchodilators on reducing exacerbations than LABA+ICS therapy (63,78).…”
Section: Discussionmentioning
confidence: 99%
“…In a Cochrane database review of fluticasone furoate and vilanterol versus tiotropium, no statistically significant differences were found for the improvement of symptoms in COPD assessment Test (CAT) score nor FEV 1 after 84 days. The authors Sliwka et al [42] suggested that further trials with longer duration are needed to determine if there is an advantage of either therapy since the current data is not strong enough to establish differences in efficacy or equivalency. The introduction of a PDE4 inhibitor in the addition of a LAMA or LABA here may be an alternative route to explore for the treatment of further exacerbations in Group C rather than an ICS.…”
Section: Pharmacotherapy Management For Gold Group Cmentioning
confidence: 99%
“…Both lead to more symptoms, higher hospitalization rates, lower QoL, impaired exercise capacity and poorer prognosis. 4 The principles that drove improved primary and secondary prevention of CVD complications -such as addressing risk factors (including smoking cessation 35 ), early accurate diagnosis, appropriate pharmacotherapy [36][37][38] with rapid escalation, rapid referral to other members of the COPD team (eg pulmonary rehabilitation 39 ) and patient education and self-management 40 -should reduce exacerbations.…”
Section: Introductionmentioning
confidence: 99%